Clavulina tumida (Hydnaceae, Cantharellales), a new species from Northeast China - Zeng, Ya-Ping; Shi, Zhen-Liang; Li, Mei-Jia; Sun, Pei-Si; Zhang, Ping (Phytotaxa, 2026)
The species diversity of Clavulina (Hydnaceae) is concentrated in tropical and subtropical regions, whereas comparatively few species are known in temperate regions. Based on morphological and molecular evidence, a new coralloid species, Clavulina tumida, is described from specimens collected in Northeast China. Phylogenetic analysis of a combined dataset of ITS, LSU, and RPB2 sequences employing Maximum likelihood and Bayesian inference methods revealed that the newly collected samples formed a distinct lineage within the Clavulina clade, supporting their identification as a new species. The new species is primarily characterized by basidiomata branches that become swollen and thickened with age. We provide photographs, line drawings, and phylogenetic analysis for the new species, together with a key to all known Clavulina species in China. The holotype was deposited in the Mycological Herbarium of Hunan Normal University (MHHNU).